2021
DOI: 10.1002/jso.26652
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing has greater prognostic value than sarcopenia in oesophago‐gastric cancer patients undergoing neoadjuvant therapy and surgical resection

Abstract: Background: Sarcopenia (low skeletal muscle mass), myosteatosis (low skeletal muscle radiation-attenuation) and fitness are independently associated with postoperative outcomes in oesophago-gastric cancer. This study aimed to investigate (1) the effect of neoadjuvant therapy (NAT) on sarcopenia, myosteatosis and cardiopulmonary exercise testing (CPET), (2) the relationship between these parameters, and (3) their association with postoperative morbidity and survival.Methods: Body composition analysis used singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…In the present study, a combination of CT-derived muscle measurements (CT-SS) was significantly associated with both a low VO 2 AT and peak. These observations are consistent with recent work of West et al, who reported that CT-derived muscle measurements were associated with CPET performance in patients with OG 24 and hepatopancreatobiliary cancer. 25 Therefore, the CT-SS provides an objective measure that reflects, in part, cardiopulmonary fitness and therefore a useful measure in those patients where CPET is contraindicated.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, a combination of CT-derived muscle measurements (CT-SS) was significantly associated with both a low VO 2 AT and peak. These observations are consistent with recent work of West et al, who reported that CT-derived muscle measurements were associated with CPET performance in patients with OG 24 and hepatopancreatobiliary cancer. 25 Therefore, the CT-SS provides an objective measure that reflects, in part, cardiopulmonary fitness and therefore a useful measure in those patients where CPET is contraindicated.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a retrospective from Japan demonstrated that visceral-to-subcutaneous adipose tissue area ratio (VSR) was a prognostic factor for the overall survival of elderly patients with gastric cancer after gastrectomy (33). Moreover, reduced SM-RA is independently associated with postoperative outcomes in cancer patients (35,50), which is consistent with our findings. The influence of sex factor on the relationship between sarcopenia and the prognosis of cancer is an emerging field.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we present a retrospective investigation of the influence of sarcopenia on the prognoses of GC patients who underwent radical gastrectomy. In addition to the classic indicator L3 skeletal muscle index (L3 SMI), other indexes like visceral fat area (VFA), subcutaneous fat area (SFA), visceral fat index (VFI), subcutaneous fat index (SFI), subcutaneous and visceral ratio (SV), and skeletal muscle radiation attenuation (SM-RA) were also included in our study according to previous studies (31)(32)(33)(34)(35). Moreover, we further evaluated potential sex differences in the relationship between sarcopenia and longterm survival.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies proposed that muscle function (defined by factors like hand grip strength or cardiopulmonary exercise testing) might be better in reflecting a patients’ physical function or nutritional status than skeletal muscle mass. 41 44 As skeletal muscle mass can be measured on routinely performed CT-scans, it is an easily available measure of the patients’ physical status. A more comprehensive picture of the patients’ physical and nutritional status might contribute to the prediction of postoperative outcomes in cancer patients.…”
Section: Discussionmentioning
confidence: 99%